Achalasia - Kwangbeom Park; Kee Wook Jung (Yong Chan Lee, 2022)
Achalasia is characterized by peristaltic failure and incomplete relaxation of the lower esophageal sphincter. The incidence and prevalence of achalasia increase with age, although achalasia can affect all age groups. The pathophysiology of achalasia involves the loss of inhibitory ganglion cells in the myenteric plexus of the esophagus. Its main symptoms include dysphagia, chest pain, regurgitation, and weight loss. The method of diagnosing achalasia has evolved from conventional manometry in the 1970s to high-resolution manometry in the 2010s. High-resolution manometry based on spatiotemporal plots can diagnose achalasia more precisely than conventional manometry. Moreover, novel parameters such as integrated relaxation pressure (IRP) (according to the Chicago classification) have increased diagnostic accuracy. However, cases of achalasia presenting with normal IRP have been reported. Therefore, the novel Chicago classification version 4.0 has adopted additional tests. These tests include the stress test for esophageal motor disorders, timed barium esophagography, and test using a functional lumen imaging probe that measures the distensibility of the esophagogastric junction. Achalasia was previously treated using surgical myotomy, balloon dilation, and botulinum toxin injection. However, peroral endoscopic myotomy (POEM) has recently become the mainstay treatment. POEM has a higher clinical success rate and a lower complication rate than surgical myotomy. Esophageal cancer and pulmonary conditions such as aspiration pneumonia are possible complications of achalasia. In this review, the current knowledge regarding achalasia together with novel diagnostic and therapeutic strategies are discussed.